Conhecimentos dos Estudantes de Enfermagem da Universidade Federal do Tocantins acerca das Práticas Integrativas e Complementares em Saúde: o ensino das PICS e suas relações na graduação - Almeida, Naiara Mesquita (2023)
Integrative and Complementary Health Practices (PICs) are recognized by the World Health Organization (WHO) as an important form of care that seeks to promote health using natural ways of treatment. From this perspective, the present study aimed to describe the knowledge of nursing students from the Federal University of Tocantins (UFT) about PICs during their academic training. This is a study with a qualitative approach and exploratory nature which had as participants 16 students aged between 20 and 28 years (20, 21, 22, 23, 24, 25 26 and 28), 3 enrolled in the 9th semester, 4 in the 8th semester, 3 in the 7th semester, 2 in the 6th semester, 2 in the 5th semester and 2 in the 4th semester. The research was submitted to Plataforma Brasil and appreciated by the Ethics and Research Committee of the UFT. We identified that PICs are still a topic that has been rarely addressed and experienced by students of the Nursing program at UFT. Therefore, there is a lack of preparation during their training and care practice in their supervised internships which are fragmented, thus hindering learning and comprehensive care for the population. Considering the students' previous knowledge and experiences about the PICs, they proved to have limited theoretical-practical knowledge on the subject. However, they recognized the importance of biological, psychological, spiritual and social aspects for an integral, holistic and humanized approach to the human being and showed interest in improving their knowledge on the subject. However, it is worth mentioning that this research did not seek to point out a single and/or better way to teach PICs. With this in mind, a public educational profile was created on the social network instagram (@knowingaspics) with the purpose of producing photo-stories, describing, introducing and disseminating scientific information to students, teachers, health professionals, researchers and the general public about the 29 PICs. Thus, the study was of great value, since it pointed out gaps in the teaching of PICs in the curriculum of the Nursing program at UFT, a fact that interferes with the knowledge and interest of students about these practices. However, given the increased demand for this field of activity, this study brings important reflections for students, teachers and others interested in the subject.